ANALISIS IMPLEMENTASI PROSEDUR PENGAMANAN DAN PEMELIHARAAN ASET TETAP DI BPPKAD KABUPATEN MAGELANG - M. Nuwafal Khoir; Nuwun Priyono (Transpublika Publisher, 2023)
The purpose of this study is to determine the suitability of the procedures for securing and maintaining fixed assets at the Regional Revenue, Financial Management, and Assets Agency (BPPKAD) of Magelang Regency with Permendagri No. 19 of 2016, which can be observed in the procedures for securing and maintaining fixed assets and the completeness of source documents. The type of research applied in this study is descriptive qualitative research. The results prove that BPPKAD of Magelang Regency has implemented the procedures, and the completeness of the source documents is satisfactory. Thus, the security and maintenance of fixed assets in BPPKAD of Magelang Regency, in accordance with Permendagri No. 19 of 2016, are in full compliance with the regulations.